Logística Portuária: Análise "S.W.O.T" dos portos do Mucuripe e Pecém - Souza, Heverson Inamar Araújo de (2017)
The maritime world trade has followed a vertiginous growth and integration of several global industries, which in their search for the optimization of their processes, efficiency and consequent general reduction of costs, creates an environment of fierce competition between the players of their logistics chains. The ports, as essential transit points of the international trade have obviously been inserted in this context. Within this commerce atmosphere, it is of utmost importance the constant and attentive observation of the particular performance of each business, product and services offered. It is important to be fully aware of own strengths, weakness, new opportunities, as well as the constant threats launched either by the competitors, or by the cycle of life of products and services shorter each day. This paper intends to lecture about the main concepts of the logistics of the ports, their players, the ports of Mucuripe (Fortaleza) and the Industrial and Port Complex of Pecém, their history, motivation, main characteristics, nevertheless with the main objective to appoint their competitive advantages and disadvantages, by means of the SWOT analysis. In the end, we have considered that the terminal of Pecém and the port of Mucuripe, despite their peculiarities, hold an intersection with regard the services they render and their competitive advantages, either due to the geographical proximity, or the pressure of the maritime market with larger ships and consequent demand by better logistics processes, or by the delay on the implementation of their main projects, we mean the first, with the refinery and the steel mill, which has been led to adapt to what has been offered by the market, like the general cargo in containers, the solid (mineral coal and iron ore) and liquid bulk (GNL) and then follow a track that sometimes conflicts with its initial purpose and led to a direct competition with the port of Mucuripe in Fortaleza.